Design of Antipodal Vivaldi Antenna for Medical Imaging Application - Mahendra, Daffa; Hakim, Randy Ivanal; Endarko, Endarko (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2023)
The microwave imaging (MWI) system in medical applications is commonly used to detect abnormalities in the human body. The purpose of this study was to design an Antipodal Vivaldi Antenna (AVA) for medical imaging applications using MWI. The research method used is based on the AVA design simulation of the CST Studio Suite 2019 application using time and frequency domain methods, which has dimensions of 60x40 mm2 with an antenna structure that works in the frequency range of 6.3-9.6 GHz, the impedance for bandwidth is -10 dB, using Flame Retardant-4 (FR-4) thickness 1.6 mm (= 4.3, tan ? = 0.025) as substrate material. A linear array of antennas was utilized in the simulation, either with or without a phantom. The phantom options include an absence of a phantom (only antennas), a cube-shaped water phantom, and a water phantom containing an anomaly. The result of the simulation on the AVA design produces a bandwidth of 41.61%, a gain of 5.16 dB, a return loss of -26.73 dB, a Specific Absorption Rate (SAR) value of 0.26 W/kg and a graph of S-parameters (S21). It can be concluded that the MWI system using the AVA design in this study has the potential to properly detect the presence of anomalies.